Duck in the truck - Alborough, Jez (HarperCollins London, 2000)
*Duck in the Truck* is a fun and lively rhyming story about a duck who gets stuck in a muck-filled truck while on an adventure. With the help of his animal friends, Duck learns that teamwork and quick thinking can solve even the stickiest of problems.